2016
DOI: 10.1089/lap.2016.0118
|View full text |Cite
|
Sign up to set email alerts
|

Early Laparoscopic Radiofrequency Ablation for Spontaneous Rupture of Hepatocellular Carcinoma

Abstract: Early laparoscopic RF ablation therapy is an effective treatment measure for spontaneously ruptured HCC in selected patients, which presents an advantage of achieving simultaneous hemostasis, tumor elimination, and rinsing of peritoneal cavity to minimize the risk of peritoneal metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Searching the reference list (snowball procedure) retrieved two additional articles. In total, 67 studies were deemed eligible and therefore included in the systematic review …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Searching the reference list (snowball procedure) retrieved two additional articles. In total, 67 studies were deemed eligible and therefore included in the systematic review …”
Section: Resultsmentioning
confidence: 99%
“…The mean age of the study population was 55.6 years (SD = 6.64) with most patients being male (77.9%). A large portion of the cohort population consisted of patients from Asia, as 22 studies (33%) were from China, 17 (25%) from Japan, 10 (15%) from Taiwan, 5 (7.5%) from Korea, 2 (3%) from Thailand, and 1 (1.5%) each from Singapore and Malaysia . In contrast, studies about rHCC were less common from Western centers with only 2 reports (3%) from the Netherlands and Italy, and 1 (1.5%) each from Canada, France, United Kingdom, USA, and Nigeria .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 As locoregional ablative therapy use became more widespread as a definitive treatment for HCC, open radiofrequency ablation (RFA) to treat rHCC emerged as a means to simultaneously achieve hemostasis and ablate tumor. 30,31 Used in conjunction with laparotomy only if ongoing blood loss after conservative treatment or TACE, one series demonstrated effective hemostasis and improved overall survival with RFA. 32 Similarly, MWA has been successfully employed to control intra-operative hepatic hemorrhage, although routine use for concomitant hemorrhage and tumor treatment has not (to current knowledge) been reported outside of this institution.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that even when peritoneal recurrence does occur following resection of a srHCC, laparoscopic extirpation of the peritoneal metastatic lesions can be effectively performed even if the index surgery was performed open. [ 31 ] There are also reports of successful local ablation of srHCC in the emergency setting via laparoscopic-guided RFA[ 32 ] and microwave ablation. [ 33 ]…”
Section: Discussionmentioning
confidence: 99%